Bangladesh Development Update, October 2019 : Tertiary Education and Job Skills - World Bank (World Bank, Dhaka, 2019)
Bangladesh economic expansion continued in FY19, supported by rising exports and record remittances. Inflation remained within the 5.5 percent target, supported by bumper rice harvests. Broad money growth increased marginally. Private sector credit growth was weak and bank liquidity remains constrained. Non-performing loans continued to rise in the banking sector. The current account deficit declined with higher export and lower import growth. Bangladesh Bank interventions moderated the depreciation of the taka against the US dollar, but the real effective exchange rate appreciated. The fiscal deficit has reached 4.6 percent of GDP as expenditure increased and revenue collection remained below target. Recent tax policy adjustments are likely to constrain revenue growth in the near term, while additional subsidies will increase recurrent expenditure. Sustaining growth will require momentum on the reform agenda to address challenges in the business climate, public investment management, revenue mobilization, and the resolution of fragile banks. Economic transformation will require development of new skills in the workforce. Tertiary educational institutions can support this agenda if quality, relevance, and access challenges are addressed.